2021
DOI: 10.1111/dme.14668
|View full text |Cite
|
Sign up to set email alerts
|

Glycated haemoglobin (HbA1c), diabetes and neuropsychological performance in community‐dwelling older adults

Abstract: Aims Given that diabetes is associated with cognitive impairment and dementia in later life, we aimed to investigate the relationship between glycated haemoglobin (HbA1c), diabetes and domain‐specific neuropsychological performance in older adults. Methods Cross‐sectional cohort study using data from the Trinity‐Ulster‐Department of Agriculture (TUDA) study. Participants underwent detailed cognitive and neuropsychological assessment using the Mini‐Mental State Examination (MMSE), Frontal Assessment Battery (FA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Testing lasted 60–70 min and included the following tasks: (i) paired-associates learning (PAL)—memorising geometric patterns on screen and results were given as first-attempt memory score (PAL-FAMS; range 0–20); (ii) spatial working memory (SWM)—memorising locations on screen to uncover hidden tokens with results as strategy score (SWMS; range 2–12); (iii) pattern recognition memory (PRM)—recall of specific geometric patterns after a 20 min delay scored as percentage correct delayed (PRMPCD; range 0–100%); (iv) reaction time task–reaction time to circles on screen in ms; (v) rapid visual processing (RVP)—detecting sequences of numbers amongst a rapidly changing series of digits measured as a signal detection or “A prime” measure (RVPA; range 0.00–1.00); and (vi) one-touch stockings of Cambridge (OTS)—matching patterns by moving coloured balls inside stockings in the minimum number of moves assessed as “problems solved on first choice” (OTSPSFC; range 0–15). These tests were selected to assess immediate and delayed memory and the attention and executive function domains, which are amongst the earliest affected in T2DM-related cognitive dysfunction [ 22 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Testing lasted 60–70 min and included the following tasks: (i) paired-associates learning (PAL)—memorising geometric patterns on screen and results were given as first-attempt memory score (PAL-FAMS; range 0–20); (ii) spatial working memory (SWM)—memorising locations on screen to uncover hidden tokens with results as strategy score (SWMS; range 2–12); (iii) pattern recognition memory (PRM)—recall of specific geometric patterns after a 20 min delay scored as percentage correct delayed (PRMPCD; range 0–100%); (iv) reaction time task–reaction time to circles on screen in ms; (v) rapid visual processing (RVP)—detecting sequences of numbers amongst a rapidly changing series of digits measured as a signal detection or “A prime” measure (RVPA; range 0.00–1.00); and (vi) one-touch stockings of Cambridge (OTS)—matching patterns by moving coloured balls inside stockings in the minimum number of moves assessed as “problems solved on first choice” (OTSPSFC; range 0–15). These tests were selected to assess immediate and delayed memory and the attention and executive function domains, which are amongst the earliest affected in T2DM-related cognitive dysfunction [ 22 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Given that executive function is one of the first domains affected in individuals with T2DM and other cardiovascular risk factors, the incorporation of dual-task conditions into gait assessments may be beneficial in the identification of those most at risk. [ 22 , 23 ]. Apart from introducing an additional task to single-task paradigms, assessing maximal gait speed (and not just usual gait speed) may also reveal differing associations with neurocognitive function in older adults—and potentially may have a role in probing executive function in particular [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…TUDA participants aged 60+ years, without a diagnosis of dementia at initial assessment, were recruited from geriatric medicine day hospital/outpatient clinics in St James's Hospital Dublin, Ireland, and from general practice in the Western and Northern Health and Social Care Trust catchment areas in Northern Ireland. Further details on the TUDA dataset are available in other studies, including investigations of risk factors for cognitive dysfunction [32][33][34][35] and depression and anxiety disorders [36].…”
Section: Mental Health Assessment and Risk Factorsmentioning
confidence: 99%
“…These studies used screening level tools (MMSE, MoCA) to assess cognitive function which gives a limited understanding of changes in different cognitive domains. Few studies that assessed cognitive domains in-depth found deficits in executive function (Pappas et al, 2017), processing speed and working memory (meta-analysis, Mansur et al, 2018), and memory, language, attention, and visuo-spatial abilities (Dyer et al, 2021). A large UK cohort study by Antal and colleagues (2022) also observed deficits in executive function and processing speed in type-2 diabetes and found gray matter atrophy and altered brain activity across many brain areas, a sign of accelerated aging.…”
Section: Introductionmentioning
confidence: 99%